2017
DOI: 10.1155/2017/8180272
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Social Unrest Events with Hidden Markov Models Using GDELT

Abstract: Proactive handling of social unrest events which are common happenings in both democracies and authoritarian regimes requires that the risk of upcoming social unrest event is continuously assessed. Most existing approaches comparatively pay little attention to considering the event development stages. In this paper, we use autocoded events dataset GDELT (Global Data on Events, Location, and Tone) to build a Hidden Markov Models (HMMs) based framework to predict indicators associated with country instability. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 19 publications
1
35
0
Order By: Relevance
“…As our case-studies and other research drawing on GDELT has demonstrated (e.g., Qiao et al, 2017;Vargo, et al, 2018), GDELT does provide meaningful, valid insights into larger societal trends and news coverage patterns. Second, communication researchers using iCoRe to obtain computationally derived content-analytic measures must be conscious of the opportunities and shortcomings that underlie these methods .…”
Section: Limitationssupporting
confidence: 61%
See 2 more Smart Citations
“…As our case-studies and other research drawing on GDELT has demonstrated (e.g., Qiao et al, 2017;Vargo, et al, 2018), GDELT does provide meaningful, valid insights into larger societal trends and news coverage patterns. Second, communication researchers using iCoRe to obtain computationally derived content-analytic measures must be conscious of the opportunities and shortcomings that underlie these methods .…”
Section: Limitationssupporting
confidence: 61%
“…In light of GDELT's massive datasets, GDELT's data has been integrated into Google BigQuery, a web service designed to store and provide access to large-scale datasets through standard SQL queries. Accordingly, the majority of studies accessing GDELT have utilized Google BigQuery (e.g., Qiao et al, 2017) or developed independent scripts that download and parse the raw GDELT data in comma-separated value (CSV) format to address a specific research question (e.g., . While Google BigQuery provides unprecedented querying speed, it is a fee-based service that can quickly become expensive with increasingly data-heavy operations.…”
Section: The Gdelt Interface For Communication Research (Icore)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some articles criticized this method of content classification as keywords alone cannot decide the relativity of content to civil unrest. Instead, they used keyword dictionary for filtering and the popular supervised classifiers like SVM (Chen & Neill, 2014;Korolov et al, 2016;Qiao & Wang, 2015), Naïve Bayes (Qiao et al, 2017;Ramakrishnan et al, 2014;van Noord, Kunneman, & van den Bosch, 2016) and n-gram classifier (Compton et al, 2014) for classification of content. An exception, Ranganath et al (2016) used the latent discriminant classifier based on extracted latent dimension representation of content to identify related content.…”
mentioning
confidence: 99%
“…However, these frameworks suffer from the fact that nowadays protestors are smart and rarely specify dates of their planned events directly in their posts. In view of this limitation, other authors use regression techniques like logistics and Least Absolute Shrinkage and Selection Operator (LASSO) regression (Cadena et al, 2015;Korkmaz et al, 2015;Korolov et al, 2016;Qiao & Wang, 2015;Ramakrishnan et al, 2014;Wu & Gerber, 2018), HMM (Hidden Markov Model) (Qiao et al, 2017), random forest (Singh & Pal, 2018) and Long Short-Term Memory Networks (LSTM) (Galla & Burke, 2018) in predicting tasks that use historical event information. The rest of the authors introduce their own prediction models like data mining frameworks based indication and warning assessment, recognition system (IWARS) (Benkhelifa, Rowe, Kinmond, Adedugbe, & Welsh, 2014), graph-based non-parametric heterogeneous graph scan (NPHGS) model (Chen & Neill, 2014) and multi-task learning framework based Multi-Task Feature Learning (MTFL) model (Zhao et al, 2017), Bayesian model fusion framework (Hoegh, Leman, Saraf, & Ramakrishnan, 2015), Naïve Bayes (Hossny & Mitchell, 2018), and keyword frequency-based model (Manrique et al, 2013).…”
mentioning
confidence: 99%